SOCIOCULTURAL DEVELOPMENTAL FACTORS OF PRESCHOOL CHILDREN IN MODERN SITUATION - Nesyna, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This work presents kindergarten teachers’ ideas of the most important sociocultural developmental factors of preschool children in modern situation. Essay as a data-gathering tool was applied. According to the results, the main sociocultural factors are both family and kindergarten. Developmental value of the play, children's community and communication with peers are underestimated by kindergarten teachers. Teachers give preference to cognitive development, while personal development becomes secondary. Early connection of children to information space and technologies is still not comprehended completely, although kindergarten teachers describe some problematic aspects of this phenomenon.